The interphase and thermal conductivity of graphene oxide/butadiene-styrene-vinyl pyridine rubber composites: A combined molecular simulation and experimental study. (1st March 2020) - Yang, Hailong; Cai, Fei; Luo, Yanlong; Ye, Xin; Zhang, Chen; Wu, Sizhu
Abstract: In this study, how the oxidation degree of graphene oxide (GO) affects the dispersion of GO and the interfacial adhesion in butadiene–styrene–vinyl pyridine rubber (VPR)/GO composites, as well as the interfacial thermal transport were investigated by molecular dynamics simulation. Subsequently, the composites containing different oxidation degrees of GO were prepared by the chemical reduction GO in situ to verify the theoretical predictions and explore the relationship between the microstructures and macroscopic performance. The results showed that with the increase of oxidation degree of GO, the compatibility between GO and VPR improved first and then reduced, while the interface interaction enhanced gradually. The best oxidation degree of GO was acquired at about 15%, for which case the optimal dispersion of GO, the best mechanical properties and highest thermal conductivity of the composites are achieved. Although increasing the oxidation degree of GO can reduce the interfacial thermal resistance, the decreased intrinsic thermal conductivity and re-aggregation of GO with high oxidation degree would limit the increase in thermal conductivity of the composites. This study may provide a valuable guidance for chemical modifying graphene surface to optimize the GO/rubber composite properties.